Biopsychosocial factors linked with overall well-being of students and educators during the COVID-19 pandemic - Saher Al-Sabbah; Amani Darwish; Najwan Fares; James Barnes; Jehad Ali Almomani (Cogent Psychology, 2021)
This study aims to explore the biopsychosocial factors linked with the well-being of students and educators during the Coronavirus Disease 2019 (COVID-19) pandemic, and how these factors affect feelings, thoughts, behavior, family relationships, and work environment. We developed a questionnaire comprising three domains: biological, psychological, and social. These three domains covered some of the symptoms that occurred in people during the COVID-19 pandemic. The sample included educators and students who were randomly selected from two countries: the United Arab Emirates (UAE) and Jordan. The sample consisted of 56 academic staff, 6 administrative staff, and 232 students at the tertiary level. The main findings showed that the most commonly reported biopsychosocial factors linked with educators’ and students’ well-being were the effect on family, depression, negative effect of media, headache, increased eating and sleep, physical comfort, and positive effect on goal achievement. In addition, the results showed that the demographic variables, gender and academic levels, had no statistically significant effect on the participants’ responses, but there was a significant effect of social status. In addition, the study highlighted the common coping strategies used by educators and students, such as doing physical exercise, finding a hobby, sleeping, and eating more meals.